Measurement of Liver Fibrosis in Chronic Hepatitis D: Comparison of Invasive and Non-Invasive Methods - Gidaagaya, Sarantuya; Dorj, Sumiya; Jamsranjav, Selenge; Dungubat, Erdenetsogt; Batmunkh, Munkhhbat; Namdag, Bira (Central Asian Journal of Medical Sciences, 2019)
Objectives: The aim of this study was to compare non-invasive methods in the detection of hepatic fibrosis in patients with chronic hepatitis delta. Methods: Twelve patients with chronic hepatitis delta who visited the Gastroenterology Department at the Intermed Hospital, were studied. Clinical and histological data were evaluated and serum indirect fibrosis markers including AST to ALT ratio, AST-to-Platelet Ratio, Fibrosis-4 index scores were calculated. Serum Mac-2 binding protein glycosylation isomer and liver stiffness measurements were performed in all participants. Results: Histological scoring showed that 16.7%, 41.7% and 41.7% of participants had F2, F3, and F4 stage of liver fibrosis, respectively. All participants were divided into groups; cirrhotic (F4) and non-cirrhotic (F0-F3). The median AST to ALT ratio in cirrhotic vs. noncirrhotic patients was 1.4 vs. 1.1 (p=.67), AST-to-Platelet ratios were 0.7 vs. 1.1 (p=.48), and Fibrosis-4 index scores were 1.8 vs. 1.6 (p=.82) in non-cirrhotic patients. Median Mac-2 binding protein glycosylation isomer levels in the cirrhotic group 1.3 cut-off index vs. 1.4 cut-off index in the non-cirrhotic group (p=.85). The median liver stiffness was 12.6 kPa in cirrhotic patients while 8.1 kPa in non-cirrhotic patients (p=.05). Conclusion: Non-invasive serum markers were less accurate in determining fibrosis in chronic hepatitis delta patients. Liver stiffness measurement was superior to the non-invasive serum markers.